Single-phase five level inverter - Sukma, Nari Amelia Aprilianti; Asnil (Journal of Industrial Automation and Electrical Engineering, 2025)
This paper presents the design and implementation of a single-phase five-level inverter using the Cascaded H-Bridge (CHB) topology. The primary objective of this research is to evaluate the inverter’s performance based on the Total Harmonic Distortion (THD) of the output voltage waveform under resistive load conditions. The proposed system consists of two H-Bridge modules powered by independent 23 V DC sources, controlled by an Arduino Mega 2560 and supported by gate driver circuits. The inverter is tested using incandescent lamp as the load. The results show a clearly stepped five-level AC output waveform, characteristic of CHB inverters. THD analysis indicates a distortion level of approximately 12.72%, which is higher than the IEEE 519 standard for sensitive equipment but acceptable for general resistive applications. The results confirm the feasibility of CHB-based inverter construction for practical use, while also highlighting opportunities for further optimization, especially in reducing harmonic content. This work contributes to the field of power electronics by providing a practical foundation for developing low-THD, cost-effective multilevel inverters.